School-Based Prevention Targeting Non-Suicidal Self-injury: A Pilot Study - Baetens, Imke; Decruy, Christine; Vatandoost, Shokoufeh; Vanderhaegen, Birgit; Kiekens, Glenn (Frontiers in Psychiatry, 2020)
Non-Suicidal Self-Injury (NSSI) is quite prevalent in adolescence and is associated with increased risk for a variety of subsequent negative mental health outcomes, necessitating an evidence-based preventive approach. The purpose of this pilot study was to examine the effects and feasibility of an evidence-based school program focusing on mental health with a focus on NSSI. Differences were examined between a general in-classroom prevention program (Happyles) and this program combined with a one-hour classroom psychoeducation module on NSSI (HappylesPLUS) in terms of primary (e.g., delay in onset and decrease in frequency, urges, probability of future engagement) and secondary outcomes (e.g., psychological distress, emotion regulation, help seeking and stigma). A total of six secondary schools and 651 students participated. Participating classes were randomly assigned to each condition. A total of 651 middle-school pupils (Mage = 12.85 years; 49.8% female versus 50.2% male) were assigned to the Happyles program and HappylesPLUS. Participants filled out validated self-report questionnaires before and after the preventive programs, including the Youth Outcome Questionnaire (YOQ), the Brief Non-Suicidal Self-Injury Assessment Test (BNSSI-AT), the Difficulties in Emotion Regulation Scale (DERS), the Attitudes Toward Seeking Professional Psychological Help Scale - Short Form (ATSPPH-SF) and the Peer Mental Health Stigmatization Scale (PMHSS). Overall, results show no iatrogenic effects of the NSSI focused psychoeducation module. In terms of primary outcome, both groups reported reduced likelihood of future NSSI engagement. The main results with regard to secondary outcome are increased emotional awareness in both groups. The qualitative data suggest that the NSSI specific module, for some students, has benefits directly related to NSSI, such as de-stigmatization of NSSI, NSSI awareness and increased likelihood that students would encourage peers who engage in NSSI to seek support. This pilot study shows that incorporating NSSI-specific modules into evidence based school prevention programs is feasible, does not lead to iatrogenic effects, and may increase awareness of and peer-support for students with NSSI experience. These findings inform future studies and suggests that efforts to develop evidence-based prevention programs for NSSI will be fruitful. It also identifies factors likely to be of import in future studies of this nature.